SEPTIC STATE IN THE DIFFERENTIAL DIAGNOSIS OF FEVER OF UNKNOWN ORIGIN - Ilić, Luka; Jeremić, Aleksandar (Srpski medicinski časopis Lekarske komore, 2024)
Introduction: In the modern world, fever of unknown origin is becoming an increasingly common entity with varied etiologies. Septic condition has a significant role as an etiological factor of fever of unknown origin, often being overlooked or treated late. Objective: To determine the frequency of sepsis, to establish demographic characteristics, clinical presentation of the disease, to identify the proportion of proven pathogens and their distribution by type, and to present laboratory analyses of patients diagnosed with sepsis upon admission and discharge from the hospital. Materials and Methods: The study included patients treated at the Clinic for Infectious and Tropical Diseases of the Clinical Center of Serbia, in the Department of Clinical Pharmacotherapy, from December 1, 2014, to December 31, 2017, with documented sepsis during the investigation of the etiology of FUO. Results: Among 420 patients studied, sepsis was documented in 50 (11.9%). The study included 29 (58%) women and 21 (42%) men, with an average age of 63.76 ± 13.6 (24-90) years. The causative agent of the disease was detected in blood cultures in 40 (80%) patients, while not in 10 (20%). Elevated body temperature occurred in 49 (98%) patients, whilst 24 (47%) experienced chills and shivering, 13 (25.5%) nausea, and 16 (31.4%) vomiting. Headache occurred in 8 (16%) patients, while diarrhea, urinary symptoms, and altered consciousness were observed in 11 (21.6%) patients. By comparing the median values of biochemical analyses of patients obtained upon admission and discharge from the hospital, a statistically significant difference (p<0.01) was found, indicating a decrease in laboratory parameter values such as erythrocyte sedimentation rate, C-reactive protein, total leukocyte count, and percentage of segmented leukocytes. Conclusion: In the observed sample, sepsis occurs relatively frequently (11.9%) as an etiological factor of FUO. In the differential diagnosis of fever of unknown origin, despite significant progress and development of sophisticated diagnostic procedures, one should always consider potential systemic infection as a possible cause, among which septic condition occupies an important place, even when initial examinations do not lead to such a conclusion.